(untitled) (Indonesian Journal of Science and Technology, 2025)
Communications require a large amount of network resources to support the heavy traffic generated by the Internet of Things (IoT). As a result, microelectronics and telecommunications have been exploring types of hardware capable of supporting these new network architectures and communication systems. New devices should be designed to offer high speed, ultra-wideband connectivity, and extensive coverage. In addition, they should use eco-friendly materials to respond to the needs of sustainable smart cities and meet the requirements of future communications. This literature review followed the PRISMA statement to identify research trends in the use of graphene in antennas for wireless communication applications. A total of 168 documents were analyzed, and one of the main findings is a considerable rise in research interest in this topic since 2012, with India emerging as the leading contributor of knowledge in this area. Furthermore, most applications have been developed for the terahertz band, and more recent studies have focused on utilizing MIMO technologies for 5G and 6G communication systems. In addition, most research has observed improvements in the performance and efficiency of antennas designed with graphene, observing in some results up to 9.35 dBi of gain and 97.6% in radiation efficiency for applications in the terahertz band.